Pengaruh Kualitas Pelayanan Koperasi Syariah Benteng Mikro Indonesia Terhadap Kepuasan dan Loyalitas Anggota - Edi, Sarwo; Tanjung, Hendri; Ibdalsyah, Ibdalsyah (Journal of Business Inflation Management and Accounting, 2025)
The problem that was used as the object of the research is that in the operational journey carried out by Kopsyah, BMI for the past 5 years in providing services to members was very maximal and this could not be proven with supporting data, from the financial statements that members could quit , the need for this research was made to find out from the form of satisfaction and loyalty of members in Kopsyah Benteng Mikro Indonesia. This study aims to 1) Know the Effect of Service Quality on Member Satisfaction in Kopsyah Benteng Mikro Indonesia 2) Know the Effect of Service Quality on Loyalty of Koperasi Benteng Mikro Indonesia’s Members 3) Know the Effect of Member Satisfaction on Loyalty of Koperasi Benteng Mikro Indonesia’s Members. The data collection technique is use a questionnaire given to respondents (members) of 457 people. The population in this study is a member of the BMI Sharia Cooperative who has a membership period of at least 2 years in Kopsyah BMI. The sampling technique uses Simple Random Sampling from all members who have been members for at least 2 years. The analytical tool used is SPSS 20. The results of the study showed that the service quality of Kopsyah Benteng Mikro Indonesia had an effect on member satisfaction and loyalty.